The chicken--a laboratory animal of the class Aves - Plachý, J (Folia biologica, 2000)
Prague inbred lines of chickens represent a unique system of MHC(B) congenic partners differing in the immune-based resistance/susceptibility to v-src-induced oncogenesis. Mapping in chickens can be facilitated by the availability of inbred lines, since many well described differences in disease susceptibility and MHC(B) haplotypes exist among the defined lines. Long-term intensive research on human, mouse, and rat MHC has established a canonical picture of this multigene complex. The chicken MHC(B) is clearly the best characterized outside the mammals and it was the first MHC clearly different from the paradigmatic structure of the above mentioned mammalian species. Chickens were in many aspects the poor relatives of mice, and they had to wait for introduction of molecular biology methods. But, when it happened, the newly gained data could be easily reconciled with classical genetic studies using available congenic chicken lines. We have established permanent tumor cell lines from ex vivo tumors induced by the LTR, v-src, LTR provirus in inbred chickens. These cells express a high level of the v-src oncogene and are of defined MHC(B) genotype. We witness a dramatic acceleration of the development of chicken (avian) genomics. The chicken is not only a good comparative model for basic science, but it is also an object of the poultry industry, which is threatened by several avian diseases. The reason for genome mapping in chickens is thus more than academic.
Keywords: kur domácí; modely nemocí na zvířatech; geny src; Male; Genes, src; Chickens; Neoplasms, Experimental; mužské pohlaví; Inbreeding; hlavní histokompatibilní komplex; inbreeding; krysa rodu Rattus; genom; Animals; lidé; experimentální nádory; ženské pohlaví; Humans; zvířata; Recombination, Genetic; Rats; Disease Models, Animal; rekombinace genetická; myši; nádorové buňky kultivované; Genome; Tumor Cells, Cultured; Mice; Female; zvířata kongenní; Major Histocompatibility Complex; Animals, Congenic